Diagnostic Performance of Ultrasound Elastography and Serologic Fibrosis Indices for Evaluation of Hepatic Involvement in Wilson Disease. (13th May 2020) - Hwang, Jisun; Yoon, Hee Mang; Jung, Ah Young; Lee, Jin Seong; Kim, Kyung Mo; Oh, Seak Hee; Cho, Young Ah
Abstract : Objectives: To investigate the diagnostic value of transient elastography (TE), 2‐dimensional (2D) shear wave elastography (SWE), and the serologic fibrosis indices aspartate transaminase–to–platelet ratio index (APRI) and Fibrosis‐4 (FIB‐4) score for Wilson disease (WD). Methods: We retrospectively identified patients with a diagnosis of WD who underwent TE and 2D SWE on the same day. Their APRI and FIB‐4 scores were calculated. Hepatic involvement was classified into 5 clinical categories (I–V) based on the laboratory findings, hepatic morphologic characteristics on ultrasound (US) imaging, and clinical symptoms of cirrhosis: I, normal (n = 17); II, only biochemical abnormality (n = 15); III, altered hepatic morphologic characteristics (n = 10); IV, compensated liver cirrhosis (n = 3); and V, decompensated liver cirrhosis (n = 0). We compared the area under the receiver operating characteristic curve (AUROC) data for TE, 2D SWE, the APRI, and the FIB‐4 score. A combined assessment of the serologic markers and US elastography was performed, and the AUROCs of the combinations were compared. Results: Forty‐five patients were included in the study (median age, 16.0 years; range, 3–35 years). Transient elastography, 2D SWE, and APRI were comparable in distinguishing the clinical categories (AUROC, 0.799–0.928). The FIB‐4 score showed lower diagnostic value in distinguishing clinical category I from the other categories (AUROC, 0.647). Combining the serologic markers and US elastography significantly increased the AUROC value of the FIB‐4 score (with TE and 2D SWE, P = .01 and .02). Conclusions: Transient elastography and 2D SWE showed excellent diagnostic accuracy for differentiating the clinical categories of hepatic involvement. The APRI showed better diagnostic performance than the FIB‐4 score. The assessment of hepatic manifestations in WD can be improved by combining US elastography with serologic indices.